A comparative study of spontaneously conceived twin pregnancies vs. twins conceived by assisted reproductive techniques and their maternal and perinatal outcomes: a prospective observational study - Nazneen, Sarah; Kandasamy, Vijayalakshmi; Shinde, Ranoji V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The utilization of assisted reproductive techniques has led to a notable increase in the incidence of twin pregnancies. Neonates from multifetal gestations also make up a disproportionate percentage of very-low-birthweight newborns and have increased risks of having congenital malformations and preterm birth. This study was done to compare the maternal and and perinatal outcomes of spontaneously conceived twins and those twins conceived by assisted reproductive techniques. Methods: The present hospital based observational study was done at Chettinad Hospital and Research Institute, Chennai, India over a period of 36 months between February 2021 to January 2024 among pregnant women with twin gestation attending the outpatient department during the study period. 50 antenatal mothers with twin pregnancy and 50 pairs of twins were studied. Convenient sampling technique was adopted. The subjects were followed up from the booking visit, till the postpartum discharge day. Any adverse maternal, foetal, neonatal outcomes and the treatment given were studied. Results: The mean birth weight among those with spontaneous conception and assisted reproductive techniques conception was 2.23±0.46 kgs and 2.02±0.51 kgs, respectively. Both the groups were similar with regard to the birth weight. 6.6% babies from the spontaneous conception group and 5% from the assisted reproductive techniques conception group were admitted for respiratory distress and rest from both the groups got admitted for sepsis. The mean duration of hospital stay was 3.58±2.40 days for the spontaneous conception group and 3.75±2.71 days for assisted reproductive techniques conception. Conclusions: This study concludes that the maternal and fetal outcomes of twin deliveries conceived spontaneously or through assisted reproductive techniques do not differ significantly in their outcome.